KEMAMPUAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU - Adriantoni, Adriantoni; Atmaja, Tirga (UIN Imam Bonjol Padang, 2023)
The purpose of this study was to find out how the headmaster ability to improve the performance of Islamic Education Teachers in Pedagogic competence, Professional Competence, and the unsupporting faktors and supporting of the headmaster to improve the performance of Islamic Religious Education Teachers in Pedagogic Competence and Professional Competence. This research is descriptive fiel research. That is giving a detailed description of the problems that are in accordance with the facts. The resources are the headmaster, vice headmaster of the curriculum section, vice headmaster of student affairs and 3 Islamic Religious Education teachers in Junior High School 5 Pariaman, east Subdistrict of Pariaman City. In the data collection the author conducted observations, interviews, and documentation studies related to the research. The findings of the study showed that the principal improved the performance of Islamic Religious Education Teachers in Pedagogic Competence in terms of understanding the teacher's insight into the foundation and philosophy of education, the teacher understood the potential and diversity of students, teachers were able to develop curriculum, teachers were able to develop learning plans and strategies, teachers were able to carry out learning which educates with a dealogical and interactive atmosphere, the teacher is able to evaluate learning outcomes, teachers are able to develop the talents and interests of students through curricular activities and extra curricular activities are enhanced through upgrading, Subject Teacher Training, educational training and workshops. Then every semester the principal conducts a Teacher Performance Assessment. Principals improve the performance of Islamic Religious Education Teachers in Professional Competency in terms of Planning learning systems, implementing learning systems, evaluating learning systems and developing improved learning systems through teacher professionalism training, workshops, seminars and Subject Teacher Consultations.